Fluorescence Anisotropy Reloaded—Emerging Polarization Microscopy Methods for Assessing Chromophores' Organization and Excitation Energy Transfer in Single Molecules, Particles, Films, and Beyond. Issue 22 (5th February 2019) - Camacho, Rafael; Täuber, Daniela; Scheblykin, Ivan G.
Abstract: Fluorescence polarization is widely used to assess the orientation/rotation of molecules, and the excitation energy transfer between closely located chromophores. Emerging since the 1990s, single molecule fluorescence spectroscopy and imaging stimulate the application of light polarization for studying molecular organization and energy transfer beyond ensemble averaging. Here, traditional fluorescence polarization and linear dichroism methods used for bulk samples are compared with techniques specially developed for, or inspired by, single molecule fluorescence spectroscopy. Techniques for assessing energy transfer in anisotropic samples, where the traditional fluorescence anisotropy framework is not readily applicable, are discussed in depth. It is shown that the concept of a polarization portrait and the single funnel approximation can lay the foundation for alternative energy transfer metrics. Examples ranging from fundamental studies of photoactive materials (conjugated polymers, light‐harvesting aggregates, and perovskite semiconductors) to Förster resonant energy transfer (FRET)‐based biomedical imaging are presented. Furthermore, novel uses of light polarization for super‐resolution optical imaging are mentioned as well as strategies for avoiding artifacts in polarization microscopy. Abstract : Eliminating ensemble averaging by single‐molecule spectroscopy has stimulated further developments of the classical concepts of fluorescence anisotropy and linear dichroism. New methods and ideas are discussed regarding using polarized‐light absorption and emission for the quantitative evaluation of energy transfer and chromophores' organization in molecular ensembles and macromolecules.